“I’m the Head Zoologist!”: Integrating Science and Literacy Learning in Kindergarten with Inquiry and Animals - Moffit, Char A. (Early childhood education journal, 2025)
This qualitative multiple-case study examined kindergarten students’ engagement in science concepts and literacy learning in a classroom in which these two subjects were integrated through Concept-Oriented Reading Instruction (CORI). CORI is an instructional framework created to increase reading engagement by teaching reading comprehension strategies along with science concepts in third grade and above. This study explored a modified version of CORI at the Kindergarten level (K-CORI) to examine how this student-centered curriculum framework could be utilized to engage young learners in science concepts and literacy learning. Data analysis resulted in five metaphors that show how the students took on multiple identities while engaged in learning concepts during K-CORI. Students took on the following identities: learner as docent, learner as explorer, learner as researcher, learner as author, and learner as expert. The present study examined the benefits of utilizing the CORI framework with a focus on early literacy and contributes to the body of CORI research demonstrating the potential of utilizing K-CORI with young learners.